Patent landscape of Aquilaria species trends in sustainable agarwood agribusiness innovation - Hashim, Yumi Zuhanis Has-Yun (Philippine Journal of Science, 2025)
Aquilaria spp. is renowned for its fragrant, resin-impregnated wood, commonly known as agarwood, which is highly valued in the perfumery industry. Beyond this prized resin, the tree yields a wide range of materials – including leaves, fruits, seeds, flowers, oil, roots, branches, and hydrosol – many of which are being developed into consumer products. Despite its rich ethnobotanical history, strong market demand, and growing scientific interest, a gap remains between research and practical innovation. This study bridges that gap by analyzing 296 unique patents related to Aquilaria filed between 2010–2022 and drawn from Espacenet, WIPO PatentScope, Google Patents, and ASEAN Patentscope. Patent trends revealed that China leads global innovation, with most patents originating from companies and research institutes. Induction technologies (including high-pressure, fungal, and liquid methods) and therapeutic uses (notably anti-inflammatory and digestive-related applications) dominate the landscape. Beyond medicinal innovations, patents also highlight Aquilaria’s role in consumer products and sustainable cultivation. Notably, half of the patents specify the inoculation status of the agarwood material used, a critical but inconsistently reported factor that affects downstream applications. Beyond tracking innovation, these findings spotlight Aquilaria’s untapped potential in pharmacology and consumer markets. They also underscore the urgent need to align commercialization with conservation, guiding stakeholders toward sustainable cultivation and agribusiness practices that secure both industry growth and the future of this endangered species.